(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The Internet of the Things is a network that connects various gadgets and technologies without requiring human interaction. As a consequence, cities that are wiser (or more intelligent) may be constructed all over the globe. The iot technology has accelerated the development of intelligent city systems enabling sustainable living, greater comfort, including effectiveness for people by hosting multiple technologies and allowing interactions among them. Smarter Cities’ Internet of Things covers a broad range of issues but is driven by a variety of technologies. The above article provides a detailed review of the Web of Things in the Smart Cities. The major elements of something like the IoT-based Sustainable Urban landscape are first investigated, following by the technology that allows these domains to emerge in term of machine learning, algorithms, architectures, including network technology used in IoT-based Smart City platforms. Following that, a look at the most frequent methodologies or applications in several Smart City industries is presented. Finally, the challenges that IoT networks for smart - city confront, as well as ideas for overcoming them.